Satellite imagery evidence for a multiannual water level decline in Hulun Lake, China, with suggestions to future policy making responses - Li, Chunlan; Leal Filho, Walter; J. Nagy, Gustavo; Wang, Jun; Ciani, Adriano; Sidsaph, Henry; Fedoruk, Mariia; Yin, Shan; Bao, Yuhai; Ayal, Desalegn Yayeh; et al. (DIE ERDE – Journal of the Geographical Society of Berlin, 2019)
Lakes are ecosystems characterised by a substantial vulnerability to climate change. Their geomorphological features mean that they are particularly exposed to extreme events, which are known to put a significant pressure on fauna, flora and human populations. An example of the impacts of climate change on lakes can be taken from Hulun Lake, China, whose water levels have changed over time due to the combined impact of climate extremes and anthropogenic activities. There is a limited amount of literature on Hulun Lake and a perceived need to monitor, document and disseminate information on how water level changes influence such ecosystems. This paper attempts to address the current information needs by reporting on a study, which lists the pressures and stressors Hulan Lake is exposed to and considers the role of policy-making in addressing them. The methods used in this paper and the results obtained may serve the purpose of encouraging similar studies elsewhere.